A prospective cohort study on the challenge to return to work after hospitalisation in Brazil. (20th August 2020) - Motizuki, Camila S.; Maluf, Eliane M. C. P.; Simonelli, Angela P.; Petterle, Ricardo R.
Abstract: After hospital discharge, workers are expected to return to work (RTW). However, the ability to return and any possible limitations after returning are unclear. Will they be able to RTW? Do they face limitations? This is a prospective cohort study with descriptive analysis aimed to investigate the RTW during 1 year following hospital discharge and to identify any limitations faced by the workers. Data collection occurred between February 2017 and July 2018 in an Internal Medicine Unit at a General Hospital. Convenience sampling was used, and participation was voluntary. Participants comprised 170 adults. Participants' RTW and limitations were followed for 1 year after discharge. During hospitalisation, 95.9% of participants planned to RTW. However, only 30% and 34.1% had returned after 1 month and 1 year respectively. Initially, 57.6% did not believe that they would present any limitation after discharge. However, 85.3% experienced restrictions after 1 month, and after 1 year this percentage rose to 88.2%. A correlation was found between young adults and RTW. The presence of limitations increased non‐RTW risk. Therefore, it is recommended that the worker role should not be merely replaced by that of a patient, but it deserves attention of the latter in order to RTW activities. The work‐return process must focus on understanding, treating and monitoring workers' limitations over time.